2019
DOI: 10.1172/jci.insight.128308
|View full text |Cite
|
Sign up to set email alerts
|

Dietary carbohydrate restriction improves metabolic syndrome independent of weight loss

Abstract: Conflict of interest: JSV receives royalties for low-carbohydrate nutrition books. He is founder, consultant, and stockholder of Virta Health Corp.; a member of the advisory boards for Atkins Nutritionals Inc., UCAN Co., Ketone Sciences, and Axcess Global; and has received honoraria from Metagenics and Pruvit. SDP receives royalties for low-carbohydrate nutrition books. He is founder and stockholder of Virta Health Corp. and a member of the advisory board for Atkins Nutritionals Inc. RMK has had investigator-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
133
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 169 publications
(151 citation statements)
references
References 53 publications
13
133
1
4
Order By: Relevance
“…Studies have shown that BA regulates serum biochemical indicators in HFD fed mice [35,36]. The high-fat diet significantly increased the total cholesterol (TC), triglyceride (TG), high density lipoprotein (HDL), and low-density lipoprotein (LDL) levels in HFD group compared with those observed in the C group (Fig.…”
Section: Serum Analysis and Liver Injurymentioning
confidence: 89%
“…Studies have shown that BA regulates serum biochemical indicators in HFD fed mice [35,36]. The high-fat diet significantly increased the total cholesterol (TC), triglyceride (TG), high density lipoprotein (HDL), and low-density lipoprotein (LDL) levels in HFD group compared with those observed in the C group (Fig.…”
Section: Serum Analysis and Liver Injurymentioning
confidence: 89%
“…Similarly, reports of reductions in blood pressure and antihypertensive medication usage in observational studies and non-randomized trials are encouraging [75,76], but need to be assessed in prospective controlled trials. Conversely, there is good trial evidence that in patients with metabolic syndrome, adopting a low carbohydrate ketogenic diet is superior to other dietary strategies at improving lipid profiles [27,77].…”
Section: Clinical Effects Of Nutritional Ketosismentioning
confidence: 99%
“…Carbohydrate intake stimulates insulin secretion, promoting fat storage and strongly inhibiting adipose tissue lipolysis and fatty acid oxidation. In this way, low-carbohydrate diets seem to ameliorate insulin resistance and MetS [52]. Our results showed, however, that higher levels of carbohydrate intake in participants led to the lowest levels of MetSSS risk, but it is important to highlight that the kind of carbohydrate is of considerable importance, where fruits, vegetables, legumes, and whole grains are appropriate sources of carbohydrates with cardioprotective components.…”
Section: Dietary Characteristicsmentioning
confidence: 54%